Actor-Oriented Database Systems - Bernstein, Phil (Proceedings of the 2018 IEEE 34th International Conference on Data Engineering, 2018)
We present the vision of an actor-oriented database. Its goal is to integrate database abstractions into an actor-oriented programming language for interactive, stateful, scalable, distributed applications that use cloud storage. This two-page paper is a summary of the author's keynote talk at the 2018 IEEE International Conference on Data Engineering.